Military aspects of geology : fortification, excavation and terrain evaluation - Rose, Edward P. F.; Ehlen, Judy, 1944-; Lawrence, Ursula (Geological Society special publication ;, 2019)
Generated under the auspices of the society's History of Geology and Engineering Groups, this text contains papers from authors in the UK, USA, Germany and Austria. Substantial papers describe some innovative engineering activities, influenced by geology, undertaken by the armed forces of the opposing nations in World War I. These activities were reactivated and developed in World War II. Examples include trenching from World War I, tunnelling and quarrying from both wars, and the use of geologists to aid German coastal fortification and Allied aerial photographic interpretation in World War II. The extensive introduction and other chapters reveal that 'military geology' has a longer history.